Revisiting the Growth-Human Development-Poverty Nexus in Banda Aceh: Evidence from 2000 to 2024 - Talbani Farlian; M. Shabri Abd. Majid; Suriani Suriani; Meutia Handayani; M. Fatahul Dzakwan (Grimsa Journal of Business and Economics Studies, 2026)
This study revisits the relationship among regional economic welfare, human development, and poverty in Banda Aceh City, Indonesia, over the period 2000-2024. Poverty is specified as the dependent variable, while Gross Regional Domestic Product (GRDP) per capita and the Human Development Index (HDI) are specified as the independent variables. The study is situated within the growth-poverty, human development, and inclusive growth literature and is motivated by the substantial structural transformation experienced by Banda Aceh following the 2004 tsunami, post-disaster reconstruction, service-sector expansion, and post-pandemic recovery. Using annual secondary data obtained from official statistical publications and multiple linear regression analysis, the findings indicate that GRDP per capita has a positive and statistically significant association with poverty, whereas HDI has a negative and statistically significant association with poverty. The positive GRDP-poverty relationship suggests that rising average regional income has not automatically translated into pro-poor outcomes, possibly because the benefits of economic growth have been unevenly distributed or concentrated in sectors with limited absorption of low-income labor. Conversely, the negative HDI-poverty relationship underscores the importance of human capital, health, education, and welfare-enhancing capabilities in reducing poverty. This study contributes city-level evidence from Aceh and highlights the need to shift the policy emphasis from aggregate output expansion toward inclusive, labor-absorbing, and human development-oriented growth.